Peer Education Meningkatkan Perilaku dalam Mencegah Penularan Tuberkulosis Paru pada Keluarga - Sunarsih Rahayu; Ros Endah Happy Patriyani ((JKG) Jurnal Keperawatan Global, 2020)
Background: Pulmonary tuberculosis is an important public health problem in the world. In 1992, the World Health Organization (WHO) declared pulmonary tuberculosis as a "global emergency". Indonesia is committed to ending pulmonary tuberculosis as a "public health problem" in 2030. Peer education is the proper media and method to provide counseling on prevention of pulmonary tuberculosis transmission. This study was conducted to determine the effect of peer education on behavior change in preventing pulmonary tuberculosis transmission in families of ​ Sibela and Sangkrah Health Center’s work area in Surakarta. Methods: This research is a quasi-experimental study with pre post-test control group design. Data analysis using dependent t-test and independent t-test. Results: The results of the dependent t test in the intervention group showed p-value = 0,000 on knowledge, attitudes, and behavior, while the control group showed results p-value = 0.003 on knowledge, p-value = 0.057 on attitudes, and p-value = 0.004 on behavior. Independent t test shows the results of p-value = 0,000 in knowledge, p-value = 0.002 in attitudes, and p-value = 0.778 in behavior. Conclusion: Based upon these results it can be concluded that there is an influence of peer education on changes in knowledge, attitudes, and behaviors in pulmonary tuberculosis transmission prevention, as well as differences in knowledge and attitudes, but there is no difference in behavior between respondents with and without peer education.